THEORETICAL BASIS OF THE DEVELOPMENT OF SOCIAL COMPETENCE IN FUTURE SOCIOLOGISTS ON THE BASIS OF AN INTEGRATIVE APPROACH (Scientific journal of the Fergana State University, 2024)
Time requires that the future specialist has scientific and innovative potential, is flexible and sensitive to rapidly developing social changes and conditions. That is why higher educational institutions are an important condition for developing the social and professional competence of future sociologists in accordance with modern requirements, radically reforming education and raising this system to a new level of quality. This article examines the need to expand the prospects of social-professional formation in future sociologists based on an integrative approach, to determine social skills, and the most important trend in the development of the current stage of education.